An autosomal recessive mutation in SCL24A4 causing enamel hypoplasia in Samoyed and its relationship to breed-wide genetic diversity - Niels C. Pedersen; Bonnie Shope; Hongwei Liu (Canine Genetics and Epidemiology, 2017)
Abstract Background Pure breeding of dogs has led to over 700 heritable disorders, of which almost 300 are Mendelian in nature. Seventy percent of the characterized mutations have an autosomal recessive mode of inheritance, indicative of positive selection during bouts of inbreeding primarily for new desired conformational traits. Samoyed suffer from several common complex genetic disorders, but up to this time only two X-linked and one autosomal dominant disorder have been identified. Previous studies based on pedigrees and SNP arrays have concluded that Samoyed breeders have done a good job in maintaining genetic diversity and avoiding excessive inbreeding. This may explain why autosomal recessive disorders have not occurred to the extent observed in many other breeds. However, an enamel hypoplasia analogous to a form of autosomal recessive amelogenesis imperfecta (ARAI) in humans has been recently characterized in Samoyed, although the causative mutation appears to have existed for three or more decades. The rise of such a mutation indicates that bouts of inbreeding for desired conformational traits are still occurring despite an old and well-defined breed standard. Therefore, the present study has two objectives: 1) measure genetic diversity in the breed using DNA and short tandem repeats (STR), and 2) identify the exact mutation responsible for enamel hypoplasia in the breed, possible explanations for its recent spread, and the effect of eliminating the mutation on existing genetic diversity. Results The recent discovery of an autosomal recessive amelogenesis imperfecta (ARAI) in Samoyed provides an opportunity to study the mutation as well as genetic factors that favored its occurrence and subsequent spread. The first step in the study was to use 33 short tandem repeat (STR) loci on 25/38 autosomes and seven STRs across the dog leukocyte antigen (DLA) class I and II regions on CFA12 to determine the DNA-based genetic profile of 182 individuals from North America, Europe and Australia. Samoyed from the three continents constituted a single breed with only slight genetic differences. Breed-wide genetic diversity was low, most likely from a small founder population and subsequent artificial genetic bottlenecks. Two alleles at each autosome locus occurred in 70–95% of the dogs and 54% of alleles were homozygous. The number of DLA class I and II haplotypes was also low and three class I and two class II haplotypes occurred in 80–90% of individuals. Therefore, most Samoyed belong to two lines, with most dogs possessing a minority of existing genetic diversity and a minority of dogs containing a majority of diversity. Although contemporary Samoyed lack genetic diversity, the bulk of parents are as unrelated as possible with smaller subpopulations either more inbred or outbred than the total population. A familial disorder manifested by hypocalcification of enamel has been recently identified. A genome wide association study (GWAS) on seven affected and five unrelated healthy dogs pointed to a region of extended homozygosity on Canis familiaris autosome 8 (CFA8). The region contained a gene in the solute carrier 24 family (SCL24A4) that encodes a protein involved in potassium dependent sodium/calcium exchange and transport. Mutations in this gene were recently found to cause a similar type of enamel hypoplasia in people. Sequencing of this candidate gene revealed a 21 bp duplication in exon 17. A test for the duplication was in concordance with the disease phenotype. The exact incidence of affected dogs is unknown, but 12% of the 168 healthy dogs tested were heterozygous for the mutation. This population was biased toward close relatives, so a liberal estimate of the incidence of affected dogs in the breed would be around 3.6/1000. Theoretical calculations based on the comparison of the whole population with a population devoid of carriers indicated that eliminating the trait would not affect existing genetic diversity at this time. Conclusions The contemporary Samoyed, like many other breeds, has retained only a small portion of the genetic diversity that exists among all dogs. This limited genetic diversity along with positive genetic selection for desirable traits has led to at least three simple non-recessive genetic disorders and a low incidence of complex genetic traits such as autoimmune disease and hip dysplasia. Unlike many other pure breeds, the Samoyed has been spared the spate of deleterious autosomal recessive traits that have plagued many other pure breeds. However, ARAI due to a mutation in the SCL24A4 gene has apparently existed in the breed for several decades but is being increasingly diagnosed. The increase in diseased dogs is most likely due to a period of intensified positive selection for some desired conformational trait. A genetic test has been developed for identifying the mutation carriers which will enable the breeders to eliminate enamel hypoplasia in Samoyed by selective breeding and it appears that this mutation can be eliminated now without loss of genetic diversity.